Level of health laboratory service quality, service interruptions, and its predictors in public hospitals in Harar town, eastern Ethiopia - Zakir, Dire; Mekonnen, Getachaw Kabew; Negash, Belay; Marami, Dadi (Frontiers in Health Services, 2024)
BackgroundQuality laboratory services are key in the healthcare system for successful diagnosis and patient care. Uninterrupted laboratory services are needed to meet the needs of all patients and clinical personnel, but studies in developing nations revealed that most clinicians were dissatisfied due to the lack of quality laboratory services and frequent interruptions.ObjectiveThis study aimed to assess the level of health laboratory service quality, service interruptions, and its predictors in public Hospitals in Harar town, eastern Ethiopia.MethodA facility-based cross-sectional study was conducted at Hiwot Fana Specialized University Hospital and Jugel General Hospital between January and April 2024. Data collection utilized Standardized Stepwise Laboratory Improvement Process Towards Accreditation (SLIPTA) checklists and questionnaires based on the Ethiopian Hospital Standard Transformation Guidelines. Data were entered and analyzed by Statistical Package for the Social Sciences, version 26. Descriptive statistics such as frequencies, proportions, and means, were calculated. Binary and multivariable logistic regression models were applied to identify predictors with adjusted odds ratio (AOR) and a cut-off p-values <0.05 with 95% confidence interval (CI).ResultsTwo public hospital laboratories and their 54 laboratory professionals were involved in our study. According to our study, the mean score of the two public hospitals was 168.5 (61%), while Hiwot Fana specialized university hospital scored 212 (77%) and Jugel General Hospital scored 127 (46.1%). The study also revealed that out of 72 tests, 31 (43.05%) were interrupted, with clinical chemistry tests being the most interrupted (16, 51.6%) followed by Serology (7, 22.6%) and Hematology (4, 12.9%) tests. Lack of timely management response (AOR = 7.78, 95% CI = 1.48–40.83) and shortage of supplies (AOR = 60.8, 95% CI = 1.07–32.83) were significantly associated predictors of laboratory service interruptions.ConclusionNeither of the hospital's laboratories met the required score of the SLIPTA standard for quality clinical laboratory services. Moreover, laboratory service interruptions were very common in the two public hospitals in which clinical chemistry, serology and hematology tests were the most frequently interrupted. Shortage of reagents and supplies and inefficient laboratory management are the major causes of service interruptions. So, policymakers and other stakeholders should support continuous quality improvement for a better patient clinical outcome.